2021
DOI: 10.1097/md.0000000000027781
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors impacting intra- and postoperative cerebrospinal fluid rhinorrhea on the endoscopic treatment of pituitary adenomas

Abstract: We aimed to identify the risk factors associated with intra- and postoperative cerebrospinal fluid (CSF) leakage in pituitary adenomas treated with endoscopic transsphenoidal surgery. This study is a retrospective analysis of 250 pituitary adenoma cases from January 2017 to December 2019 at our hospital. All patients underwent endoscopic endonasal transsphenoidal surgeries. Univariate and multivariate analyses were performed to investigate the risk factors associated with intra- and postoperative CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Consistent with reports in the literature ( 13 , 18 ), our study showed that intraoperative CSF leak increases postoperative CSF leak rate. In this study, 107 (26.8%) patients developed intraoperative CSF leak.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with reports in the literature ( 13 , 18 ), our study showed that intraoperative CSF leak increases postoperative CSF leak rate. In this study, 107 (26.8%) patients developed intraoperative CSF leak.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, 3.5% of patients with pituitary adenomas developed cerebrospinal fluid leakage after EES. Similar to other studies ( 4 , 13 ), there was no statistically significant difference in age, gender, and Knosp grade between those with and without postoperative CSF leaks in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The destruction of the anatomical structure of the skull base is the direct cause of CSF leakage. Considering the factors of the operation itself, we got that intraoperative CSF leakage and multiple operations were associated with postoperative CSF leakage ( Figure 4 ) ( 11 , 12 , 14 – 16 , 18 20 , 26 ). There was significant statistical significance (respectively, OR = 5.61,95% CI (3.53, 8.90), P<0.00001, and OR = 2.27, 95% CI (1.60, 3.23), P < 0.00001) with no heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…There were not enough studies to evaluate the influence of age ( 10 , 25 , 26 , 28 ), tumor pathological type ( 18 , 29 ), and experience of the surgeon ( 18 ), combined with other intracranial diseases ( 23 , 30 ), albumin level ( 17 ), chronic respiratory disease ( 16 ), and diabetes mellitus ( 10 ).We can only conduct qualitative analysis based on the literature (detailed information shown in Table 3 ).There was no significant statistical difference in the impact of gender on postoperative CSF leakage.…”
Section: Resultsmentioning
confidence: 99%
“…The bi-nostril approach was used for EESBS at our institution. We performed graded skull-base reconstruction based on the surgeon's preference by predicting the risk of postoperative CSF leakage, considering the reported risk factors such as dural defect and intraoperative CSF leakage [7][8][9][10].Multilayered reconstruction using fat, fascia, and a nasoseptal ap was performed for patients with several risk factors, while simple coverage of the sphenoid sinus mucosa was performed for patients without risk factors. Rigid reconstruction was not performed at our institution.…”
Section: Surgical Proceduresmentioning
confidence: 99%